O-017 Reduction in distal emboli with proximal flow control during mechanical thrombectomy: a quantitative in vitro study. (4th July 2012) - Chueh, J; Kuhn, A; Wilson, S; Estrada, C; Gounis, M
Abstract : Purpose: The hypothesis is that proximal flow control with a balloon guide catheter (BGC) in the cervical internal carotid artery (ICA) during mechanical thrombectomy will reduce the amount of distal emboli. Materials and Methods: The model system included a true-to-scale vascular replica of the ICA/middle cerebral artery (MCA), an embolus analog (EA), and physiologically relevant flow loop. The flow loop provided a reproducible physiologic hemodynamics, and the replica was constructed based on human anatomy with moderate tortuosity to allow for realistic device tracking. The EA was injected into the system and reproducibly created an MCA occlusion. We had four experimental groups with two independent variables: 1. EA type—two EAs were used ("hard" vs "soft") 1 and 2. Use of BGC. The endpoints included the recanalization rate, the amount of flow restored and the risk of the embolic shower as indicated by the size distribution of the distal EA fragments. Characterization of the shed EA fragments produced during mechanical thrombectomy was conducted by Coulter principle, and grouped into three categories: fragments with a diameter 1. >1 mm, 2. Between 200 μm and 1 mm, and 3. <200 μm. The rate of flow restored was measured by flow sensors. A total of 40 experimental procedures were performed (n=10 per group). The Merci V-family of devices was deployed according to manufacturer's instructions. The maximum number of allotted thrombectomy attempts was 3 in each experiment. Results: All the procedures that were performed to clear the hard EA through a BGC with the use of Merci v2 soft Retriever achieved complete flow restoration (average number of passes: 1.1), giving a recanalization rate of 100%. With the absence of proximal flow control, the Merci retriever was not able to retain the hard EA within the helix loop during retrieval in 6 out of 10 experiments (40% recanalization rate, average number of passes: 2.3) regardless of the device selected (v2 soft, v2.5 soft or v2.5 firm). Dislodgement of the hard EA was frequently seen when the device was passing the ICA siphon. In our model system, the Merci V2 soft retriever achieved 100% recanalization after a single pass in all experiments with the soft EA, with or without using the BGC. Large distal emboli (>1 mm) were found in the following groups: hard EA without BGC (23 emboli), soft EA without BGC (7 emboli) and soft EA with BGC (2 emboli). Temporary proximal flow arrest significantly reduced the production of small distal emboli (<200 μm) generated from the soft EA (p<0.0001). In the groups without use of the BGC, more distal emboli (<200 μm) were generated for the hard vs the soft EA (<200 μm) (p<0.001). Conclusion: Proximal flow control reduced the number of thrombectomy attempts and increased the recanalization rate in the hard EA occlusions. As compared to the soft EA, the increased stiffness and lack of elasticity of the hard EA may account for the lower recanalization rate. The risk of distal embolization was reduced with the use of BGC. Competing interests: J Chueh: None. A Kuhn: None. S Wilson: Concentric Medical. C Estrada: Concentric Medical. M Gounis: Concentric Medical, Stryker Neurovascular. Reference: 1. Chueh et al. AJNR 2011;32 :1237.